Altered tactile localization and spatiotemporal integration in complex regional pain syndrome patients - Trojan, Joerg; Speck, Verena; Kleinboehl, Dieter; Benrath, Justus; Flor, Herta; Maihöfner, Christian (European Journal of Pain, 2019)
Background In complex regional pain syndrome (CRPS), altered perception of the affected hand and neglect-like symptoms of the affected body side are common features. In this study, we presented tactile stimuli to the affected hands in CRPS patients and matched healthy controls. Methods The participants' task was to point at the perceived positions of the stimuli using a tracking device. The spatial coordinates of the perceived positions were analysed for accuracy and consistency. We also presented patterns consisting of two stimuli at distinct positions with a delay of 100 ms. These patterns are known to induce spatiotemporal integration ("sensory saltation"). Results CRPS patients were less accurate and less consistent in the spatial perception of tactile stimuli on their hands. Furthermore, they showed increased spatiotemporal integration, although these effects were smaller than expected. These deficiencies were related to the clinically assessed intensity of recurrent pain episodes. Surprisingly, the intensity of clinically assessed ongoing pain was associated with increased precision. Conclusions In line with earlier reports, our findings indicate that the representation of the affected hands in CRPS patients is less accurate than in healthy people, probably reflecting reorganization in somatosensory cortices. The exact relationships between these findings and other aspects of CRPS remain to be elucidated. Significance: CRPS patients performed poorly in localizing positions on their affected hands via pointing and exhibited increased spatiotemporal integration. The presented method may prove useful in diagnostics as well as psychophysical and neurofunctional research on CRPS and other chronic pain disorders.
CRIS-Team WoS Importer:2019-02-27

Biochemical markers of neurodegeneration in hereditary diffuse leucoencephalopathy with spheroids - Spitzer, Philipp; Kohl, Zacharias; Gölitz, Philipp; Coras, Roland; Blümcke, Ingmar; Brueck, Wolfgang; Dörfler, Arnd; Maihöfner, Christian (BMJ Case Reports, 2014)
Hereditary diffuse leucoencephalopathy with spheroids (HDLS) is a rare autosomal dominantly inherited disease with unknown pathophysiology. Diagnosis of neurodegenerative diseases is increasingly based on biomarkers. Although lumbar puncture is routinely performed during the diagnostic workup of HDLS, reports on alterations of neurodegeneration-specific biochemical markers have not been documented so far. We report a 35-year-old woman with clinical, radiological and neuropathological signs of HDLS. She suffered from a rapidly progressive frontal lobe syndrome. Brain MRI revealed diffuse leucoencephalopathy with predominant involvement of the periventricular white matter and corpus callosum. Although she was severely impaired and leucoencephalopathy was prominent, only cerebrospinal fluid total-? was moderately elevated. Other markers of neuronal (NSE) and astrocytic (S100B) damage were within normal range. Therefore, biochemical markers of central nervous system damage are not helpful in the diagnosis of HDL
EVALuna2:7264

Blue-light treatment reduces spontaneous and evoked pain in a human experimental pain model. - Reuß, Anna Maria; Groos, Dominik; Scholl, Robert; Schröter, Marco; Maihöfner, Christian (Pain Reports, 2021)
Introduction: Chronic pain is a frequent severe disease and often associated with anxiety, depression, insomnia, disability, and reduced quality of life. This maladaptive condition is further characterized by sensory loss, hyperalgesia, and allodynia. Blue light has been hypothesized to modulate sensory neurons and thereby influence nociception. Objectives: Here, we compared the effects of blue light vs red light and thermal control on pain sensation in a human experimental pain model. Methods: Pain, hyperalgesia, and allodynia were induced in 30 healthy volunteers through high-density transcutaneous electrical stimulation. Subsequently, blue light, red light, or thermal control treatment was applied in a cross-over design. The nonvisual effects of the respective light treatments were examined using a well-established quantitative sensory testing protocol. Somatosensory parameters as well as pain intensity and quality were scored. Results: Blue light substantially reduced spontaneous pain as assessed by numeric rating scale pain scoring. Similarly, pain quality was significantly altered as assessed by the German counterpart of the McGill Pain Questionnaire. Furthermore, blue light showed antihyperalgesic, antiallodynic, and antihypesthesic effects in contrast to red light or thermal control treatment. Conclusion: Blue-light phototherapy ameliorates pain intensity and quality in a human experimental pain model and reveals antihyperalgesic, antiallodynic, and antihypesthesic effects. Therefore, blue-light phototherapy may be a novel approach to treat pain in multiple conditions.
EVALuna2:485662

Brain correlates of short-term habituation to repetitive electrical noxious stimulation - Nickel, Franziska; Ott, Sabine; Möhringer, Susanne; Saake, Marc; Dörfler, Arnd; Seifert, Frank; Maihöfner, Christian (European Journal of Pain, 2014)
Habituation to repetitive noxious stimuli is a well-known phenomenon. We investigated brain correlates of habituation to pain in a transdermal electrical pain model using functional magnetic resonance imaging (fMRI).Electrical painful stimulation with 1 Hz was applied to the volar forearm of 48 healthy subjects for 45 min. Before and after conditioning stimulation, psychophysical testing and fMRI were performed. During fMRI sessions, the subjects underwent blockwise painful electrical stimulation with a fixed percept-adapted current intensity. After fMRI 1 and fMRI 2 subjects rated the individual pain intensity of the electrical stimulus.Substantial habituation occurred during conditioning electrical stimulation. Accordingly, areas typically involved in pain processing showed decreased activity after conditioning stimulation. The blood oxygen level-dependent signal of the subgenual anterior cingulate gyrus, the superior parietal lobule and the supplemental motor area correlated positively with habituation. In contrast, activity in the periaqueductal grey, thalamus and insula correlated negatively. The results of the correlation analyses did not survive correction for multiple comparisons.With this study, we identified central components associated with habituation to repetitive painful stimuli. The results suggest that an increase in tonic inhibitory activity in cortical pain processing areas is a major mechanism contributing to habituation to phasic noxious stimuli. Moreover, areas involved in descending pain modulation were differentially modulated. This may hint at a simultaneous activation of facilitating and inhibiting nociceptive systems that are both altered in the transdermal electrical pain model.
EVALuna2:14468

Characterization of somatosensory profiles in patients with Crohn's disease - Münster, Tino; Eckl, Stefanie; Leis, Stefan; Goehring-Waldeck, Gabriele; Ihmsen, Harald; Maihöfner, Christian (Pain Practice, 2015)
Crohn's disease (CD) is a painful chronic inflammatory bowel disease. It primarily affects terminal ileum, but the involvement of large and small intestines or extraintestinal manifestations is very common. CD may go along with neurogenic inflammation, mediated by substance P and CGRP, which are also key players in pain transmission. This may in turn contribute to hyperalgesia and altered somatosensory function in CD.One hundred and three (103) patients with CD and 80 healthy volunteers were enrolled. Patient characteristics and disease history were documented. We used quantitative sensory testing (QST) to investigate the somatosensory profile in patients and volunteers. We also calculated z-scores for the QST results of the patients with CD based on the data of our control group. A 2-step cluster analysis, using all QST data, was performed to find subgroups within patients and volunteers.Thresholds of warm detection, mechanical pain, and vibration detection did significantly differ between patients with CD and volunteers. Z-scores indicated a general trend of sensory loss in CD patients with a significant relationship between patients with a sensory loss for cold and warm detection. In the hyposensitive cluster of the CD cohort, patients were more frequently male, had a higher incidence of extraintestinal manifestations, and suffered longer from CD.Our findings are consistent with the presence of a subclinical small fiber neuropathy. The group of CD patients with pronounced neuropathy findings were predominantly males, had a higher incidence of extraintestinal manifestations, and tended to have a longer history of disease duration.
EVALuna2:16687

Clinical phenotypes and classification algorithm for complex regional pain syndrome - Dimova, Violeta; Herrnberger, Myriam Selma; Escolano-Lozano, Fabiola; Rittner, Heike Lydia; Vlckova, Eva; Sommer, Claudia; Maihöfner, Christian; Birklein, Frank (Neurology, 2020)
OBJECTIVE: We pursued the hypothesis that complex regional pain syndrome (CRPS) signs observed by neurologic examination display a structure allowing for alignment of patients to particular phenotype clusters. METHODS: Clinical examination data were obtained from 3 independent samples of 444, 391, and 202 patients with CRPS. The structure among CRPS signs was analyzed in sample 1 and validated with sample 2 using hierarchical clustering. For patients with CRPS in sample 3, an individual phenotype score was submitted to k-means clustering. Pain characteristics, quantitative sensory testing, and psychological data were tested in this sample as descriptors for phenotypes. RESULTS: A 2-cluster structure emerged in sample 1 and was replicated in sample 2. Cluster 1 comprised minor injury eliciting CRPS, motor signs, allodynia, and glove/stocking-like sensory deficits, resembling a CRPS phenotype most likely reflecting a CNS pathophysiology (the central phenotype). Cluster 2, which consisted of edema, skin color changes, skin temperature changes, sweating, and trophic changes, probably represents peripheral inflammation, the peripheral phenotype. In sample 3, individual phenotype scores were calculated as the sum of the mean values of signs from each cluster, where signs from cluster 1 were coded with 1 and from cluster 2 with -1. A k-means algorithm separated groups with 78, 36, and 88 members resembling the peripheral, central, and mixed phenotypes, respectively. The central phenotype was characterized by cold hyperalgesia at the affected limb. CONCLUSIONS: Statistically determined CRPS phenotypes may reflect major pathophysiologic mechanisms of peripheral inflammation and central reorganization.
CRIS-Team Scopus Importer:2020-02-07

Does participation in art classes influence performance on two different cognitive tasks? - Schindler, Manuel; Maihöfner, Christian; Bolwerk, Anne; Lang, Frieder (Aging & Mental Health, 2016)
Objectives: Effects of two mentally stimulating art interventions on processing speed and visuo-spatial cognition were compared in three samples. Method: In a randomized 10-week art intervention study with a pre-post follow-up-design, 113 adults (27 healthy older adults with subjective memory complaints, 50 healthy older adults and 36 healthy younger adults) were randomly assigned to one of two groups: visual art production or cognitive art evaluation, where the participants either produced or evaluated art. ANOVAs with repeated measures were computed to observe effects on the Symbol-Digit-Test, and the Stick Test. Results: Significant Time effects were found with regard to processing speed and visuo-spatial cognition. Additionally, there was found a significant Time x Sample interaction for processing speed. The effects proved robust after testing for education and adding sex as additional factor. Conclusion: Mental stimulation by participation in art classes lead to an improvement of processing speed and visuo-spatial cognition. Further investigation is required to improve understanding of the potential impact of art intervention on psychological functioning across adulthood.
Keywords: subjective memory complaints; visual arts; mental stimulation; processing speed; visuo-spatial cognition

Does participation in art classes influence performance on two different cognitive tasks? - Schindler, Manuel; Maihöfner, Christian; Bolwerk, Anne; Lang, Frieder (Aging & Mental Health, 2017)
OBJECTIVES: Effects of two mentally stimulating art interventions on processing speed and visuo-spatial cognition were compared in three samples. METHOD: In a randomized 10-week art intervention study with a pre-post follow-up design, 113 adults (27 healthy older adults with subjective memory complaints, 50 healthy older adults and 36 healthy younger adults) were randomly assigned to one of two groups: visual art production or cognitive art evaluation, where the participants either produced or evaluated art. ANOVAs with repeated measures were computed to observe effects on the Symbol-Digit Test, and the Stick Test. RESULTS: Significant Time effects were found with regard to processing speed and visuo-spatial cognition. Additionally, there was found a significant Time × Sample interaction for processing speed. The effects proved robust after testing for education and adding sex as additional factor. CONCLUSION: Mental stimulation by participation in art classes leads to an improvement of processing speed and visuo-spatial cognition. Further investigation is required to improve understanding of the potential impact of art intervention on cognitive abilities across adulthood.
EVALuna2:36362

How art changes your brain: differential effects of visual art production and cognitive art evaluation on functional brain connectivity - Bolwerk, Anne; Mack-Andrick, Jessica; Lang, Frieder; Maihöfner, Christian; Dörfler, Arnd (PLoS ONE, 2014)
Visual art represents a powerful resource for mental and physical well-being. However, little is known about the underlying effects at a neural level. A critical question is whether visual art production and cognitive art evaluation may have different effects on the functional interplay of the brain's default mode network (DMN). We used fMRI to investigate the DMN of a non-clinical sample of 28 post-retirement adults (63.71 years ±3.52 SD) before (T0) and after (T1) weekly participation in two different 10-week-long art interventions. Participants were randomly assigned to groups stratified by gender and age. In the visual art production group 14 participants actively produced art in an art class. In the cognitive art evaluation group 14 participants cognitively evaluated artwork at a museum. The DMN of both groups was identified by using a seed voxel correlation analysis (SCA) in the posterior cingulated cortex (PCC/preCUN). An analysis of covariance (ANCOVA) was employed to relate fMRI data to psychological resilience which was measured with the brief German counterpart of the Resilience Scale (RS-11). We observed that the visual art production group showed greater spatial improvement in functional connectivity of PCC/preCUN to the frontal and parietal cortices from T0 to T1 than the cognitive art evaluation group. Moreover, the functional connectivity in the visual art production group was related to psychological resilience (i.e., stress resistance) at T1. Our findings are the first to demonstrate the neural effects of visual art production on psychological resilience in adulthood.

Increased prevalence of posttraumatic stress disorder in CRPS - Speck, V.; Schlereth, T.; Birklein, F.; Maihöfner, Christian (European Journal of Pain, 2017)
BACKGROUND: Although specific psychological disorders in complex regional pain syndrome (CRPS) have not been identified, studies suggest that CRPS patients may have increased rates of traumatic life events. Because these events do not always lead to apparent psychological symptoms, we systematically screened CRPS patients for posttraumatic stress disorder (PTSD) to determine if PTSD could be a risk factor for CRPS. METHODS: Consecutive CRPS patients referred to two university hospital centres (University of Erlangen, UMC Mainz) between December 2011 and April 2013 were prospectively examined using a diagnostic PTSD instrument (Post-traumatic Stress Diagnostic Scale (PDS). We also tested maladaptive coping strategies (brief-COPE inventory) and the PDS severity score as predictors for CRPS. Patients with non-CRPS extremity pain and healthy individuals were used as control groups. RESULTS: We collected data from 152 patients with CRPS, 55 control patients and 55 age- and sex-matched healthy individuals. Fifty-eight CRPS patients (38%), six non-CRPS pain patients (10%) and two healthy individuals (4%) met diagnostic criteria for PTSD. Initial PTSD symptom onset was prior to CRPS in 50 CRPS patients (86%) and during the course of CRPS in eight patients. Results of a logistic regression revealed that the PTSD severity score was associated with CRPS (p < 0.0001). Maladaptive coping strategies (p < 0.0001) were related to PTSD. CONCLUSIONS: posttraumatic stress disorder (PTSD) is more frequent in patients with CRPS than it is in the general population. SIGNIFICANCE: Research has not yet provided support for specific psychological predictors for CRPS.
EVALuna2:36547

Isolated meningomyeloradiculitis following infection with tick borne encephalitis virus - Racz, Attila; Schaller, Gerd; Lunkenheimer, Jens; Engelhorn, Tobias; Dörfler, Arnd; Sperling, Wolfgang; Schwab, Stefan; Maihöfner, Christian (Clinical Neurology and Neurosurgery, 2012)
CRIS-Team Scopus Importer:2022-08-05
Keywords: Meningomyeloradiculitis; Myelitis; Polyradiculitis; Tick borne encephalitis virus

Neuromyelitis optica presenting with relapses under treatment with natalizumab: a case report - Lee, De Hyung; Laemmer, Alexandra B.; Waschbisch, Anne; Struffert, Tobias; Maihöfner, Christian; Schwab, Stefan; Linker, Ralf (Journal of Medical Case Reports, 2014)
Neuromyelitis optica is an inflammatory demyelinating disease of the central nervous system. To date, optimal therapeutic approaches for neuromyelitis optica have yet to be defined. Natalizumab is highly effective in relapsing-remitting multiple sclerosis and might be considered as an option.Here, we describe a 67-year-old Caucasian man with definite neuromyelitis optica with detection of anti-aquaporin-4 antibodies over the course of the disease. After initially discussing the diagnosis of multiple sclerosis at an outside hospital, our patient received interferon beta 1a as well as repeated corticosteroid pulses without success. Under subsequent therapy with natalizumab, he continued to present relapses. It was not until discontinuation of natalizumab, repeated cycles of plasma exchanges and initiation of therapy with rituxan that the disease course started to stabilize. Although B cells were completely depleted, our patient experienced another severe myelitis relapse during further follow-up and an additional immunosuppressive therapy with cyclophosphamide was started. Under this regimen, no further relapses occurred over the next 24 months.This case adds further evidence to the previously discussed notion that natalizumab, while highly effective in multiple sclerosis, may not work sufficiently in neuromyelitis optica. It further advocates for repetitive testing of anti-aquaporin-4 antibodies before and after treatment initiation.
EVALuna2:22348

Possible second motor neuron damage in neuromyelitis optica - Laemmer, A. B.; Maihöfner, Christian; Gölitz, Philipp; Schwab, Sibylle; Lee, D. H.; Linker, R. A.; Schramm, Axel (Clinical Neurophysiology, 2014)
EVALuna2:22245

Serial repetitive transcranial magnetic stimulation (rTMS) decreases BDNF serum levels in healthy male volunteers - Schaller, Gerd; Sperling, Wolfgang; Richter-Schmidinger, Tanja; Mühle, Christiane; Heberlein, Annemarie; Maihöfner, Christian; Kornhuber, Johannes; Lenz, Bernd (Journal of Neural Transmission, 2014)
Although repetitive transcranial magnetic stimulation (rTMS) is established in the treatment of depression, there is little knowledge about the underlying molecular mechanisms. In the last decade, the neurotrophic hypothesis of depression entailed a plethora of studies on the role of neurogenesis-associated factors in affective disorders and rTMS treatment. In the present study, we hypothesised a sham-controlled increase of peripheral brain-derived neurotrophic factor (BDNF) levels following serial rTMS stimulations in healthy individuals. We investigated the influence of a cycle of nine daily high-frequency (HF)-rTMS (25 Hz) stimulations over the left dorsolateral prefrontal cortex (DLPFC) on serum levels of BDNF in 44 young healthy male volunteers. BDNF serum concentrations were measured at baseline, on day 5 and on day 10. Overall, the statistical analyses showed that the active and sham group differed significantly regarding their responses of BDNF serum levels. Contrary to our expectations, there was a significant decrease of BDNF only during active treatment. Following the treatment period, significantly lower BDNF serum levels were quantified in the active group on day 10, when compared to the sham group. The participants' smoking status affected this effect. Our results suggest that serial HF-rTMS stimulations over the left DLPFC decrease serum BDNF levels in healthy male volunteers. This provides further evidence for an involvement of BDNF in clinical rTMS effects.
EVALuna2:23619

Signs and Symptoms in 1,043 Patients with Complex Regional Pain Syndrome - Ott, Stephan; Maihöfner, Christian (Journal of Pain, 2018)
Complex regional pain syndrome (CRPS) is a complex pain disorder that can emerge after limb trauma or a lesion in the peripheral nervous system. Typical features include continuing pain, sensory, vasomotor, sudomotor, motor, and trophic changes as well as edema. These signs provide the basis of CRPS diagnosis. A detailed description of the signs, symptoms, and medical history of CRPS could potentially facilitate an earlier and more accurate diagnosis. The aim of this study was to provide such a description, on the basis of epidemiological measures, clinical presentation, and a thorough description of pain sensations. Some signs (eg, differences of skin temperature >1°C), which have been thought to be crucial for diagnosis, were less common than assumed. We identified 11 distinct etiological triggers, which cover more than 99% of the study participants. We developed a weighted score on the basis of the most decisive data, which achieved a sensitivity of .869 and a specificity of .829, compared with .819 and .679 for the Budapest criteria. The weighted diagnostic criteria may help to better aid in distinguishing CRPS from other pain disorders. PERSPECTIVE: This article provides a retrospective epidemiological analysis of 1,043 CRPS patients compared with 421 patients with other pain disorders. The findings could potentially facilitate a more reliable and earlier diagnosis of CRPS, a better differentiation from other pain disorders, and ultimately in a more targeted and effective therapy.
EVALuna2:213470

The serotonin receptor 2A (HTR2A) rs6313 variant is associated with higher ongoing pain and signs of central sensitization in neuropathic pain patients - Sachau, Juliane; Bruckmueller, Henrike; Gierthmühlen, Janne; Magerl, Walter; May, Denisa; Binder, Andreas; Forstenpointner, Julia; Koetting, Judith; Maier, Christoph; Tölle, Thomas R.; Treede, Rolf Detlef; Berthele, Achim; et al. (European Journal of Pain, 2020)
Background: The serotonin receptor 2A (HTR2A) has been described as an important facilitation mediator of spinal nociceptive processing leading to central sensitization (CS) in animal models of chronic pain. However, whether HTR2A single nucleotide variants (SNVs) modulate neuropathic pain states in patients has not been investigated so far. The aim of this study was to elucidate the potential association of HTR2A variants with sensory abnormalities or ongoing pain in neuropathic pain patients. Methods: At total of 240 neuropathic pain patients and 253 healthy volunteers were included. Patients were phenotypically characterized using standardized quantitative sensory testing (QST). Patients and controls were genotyped for HTR2A g.-1438G > A (rs6311) and c.102C > T (rs6313). Genotype-related differences in QST parameters were assessed considering QST profile clusters, principal somatosensory components and sex. Results: There was an equal distribution of rs6313 and linked rs6311 between patients and controls. However, the rs6313 variant was significantly associated with a principal component of pinprick hyperalgesia and dynamic mechanical allodynia, indicating enhanced CS in patients with sensory loss (−0.34 ± 0.15 vs. +0.31 ± 0.11 vs., p <.001). In this cluster, the variant allele was also associated with single QST parameters of pinprick hyperalgesia (MPT, +0.64 ± 0.18 vs. −0.34 ± 0.23 p =.002; MPS, +0.66 ± 0.17 vs. −0.09 ± 0.23, p =.009) and ongoing pain was increased by 30%. Conclusions: The specific association of the rs6313 variant with pinprick hyperalgesia and increased levels of ongoing pain suggests that the HTR2A receptor might be an important modulator in the development of CS in neuropathic pain. Significance: This article presents new insights into serotonin receptor 2A-mediating mechanisms of central sensitization in neuropathic pain patients. The rs6313 variant allele was associated with increased mechanical pinprick sensitivity and increased levels of ongoing pain supporting a contribution of central sensitization in the genesis of ongoing pain providing a possible route for mechanism-based therapies.
CRIS-Team Scopus Importer:2020-12-11

Update on structured pain assessment for the documentation of diagnosis-independent symptoms and signs associated with pain - Grömer, Teja W.; Atasever, André T.; Käfferlein, Wolfgang; Janoschka, Jonas; Moeller, Sebastian; Dohrenbusch, Ralf; Kappis, Bernd; Maihöfner, Christian; Lücke, Caroline; Kornhuber, Johannes; Philipsen, Alexandra; Müller, Helge H.O. (Schmerz, 2019)
Concerning the diagnosis and therapy of pain syndromes, standardized descriptions similar to those used in the examination of psychopathological findings via the system produced by the AMDP (“Arbeitsgemeinschaft für Methodik und Dokumentation in der Psychiatrie”, i. e., the working group establishing standardized methodology and documentation within psychiatry) are still lacking. Therefore, the authors of this article have founded a working group to establish standardized methodology and documentation for symptoms and signs associated with pain, although not at a diagnosis-specific level, in order to promote standardization in the documentation of pain and rating of the symptoms associated with a given set of medical results. This article presents a system for documenting the symptoms and signs associated with pain globally and independently of the diagnosis (Structured Pain Assessment System) with nomenclature that is inspired by the AMDP system. The objective of this working group is to develop documentation for a uniform multidimensional pain assessment (with defined terminology) that serves as a comparable and unified standard in the field.
CRIS-Team Scopus Importer:2019-06-07
Keywords: Assessment of pain; Classification; Diagnostic tool; Pain syndromes; Standardization

Varicella Zoster Virus-Specific Hyperimmunoglobulin in the Adjuvant Treatment of Immunocompromised Herpes Zoster Patients: A Case Series - Terheyden, Patrick; Sunderkötter, Cord; Söhngen, Franz Dietmar; Golle, Linda; Schimo, Sonja; Baron, Ralf; Maihöfner, Christian; Binder, Andreas; Pönisch, Wolfram (Dermatology and Therapy, 2023)
Introduction: Immunocompromised patients are at increased risk for herpes zoster (HZ)-associated complications. Despite standard therapy with systemic antiviral drugs and analgesics, complications are frequently encountered, including generalization of lesions or persistent neuropathic pain, so-called post-herpetic neuralgia (PHN). Given the scarcity of literature and awareness of therapeutic options to improve patient outcomes, especially for vulnerable patient groups, here we describe a strategy based on early intensification of treatment with a varicella zoster virus-specific hyperimmunoglobulin (VZV-IgG), which is approved in the adjuvant treatment of HZ. Methods: For this case series, we selected four cases of HZ in patients with impaired immunity due to hemato-oncologic disease or immunosuppressive treatment who presented with either existing generalized lesions and/or severe pain or with other risk factors for a complicated HZ course such as PHN. They were considered to be representative examples of different patient profiles eligible for intensification of treatment by the addition of VZV-IgG to virostatic therapy. Case Report: All patients showed a rapid response to combined treatment with VZV-IgG and a virostatic agent. In two patients who had generalized lesions, the formation of new lesions ceased 1 day after VZV-IgG infusion. One patient, with mantle cell lymphoma, achieved complete healing of the lesions 9 days after diagnosis of HZ, a rare occurrence compared to similar cases or cohorts. A patient with HZ in the cervical region showed a good response after a single dose of VZV-IgG. None of the patients developed post-zoster-related complications. Combination therapy of a virostatic agent and VZV-IgG was well tolerated in these four cases. Conclusion: This case series demonstrates highly satisfactory treatment effectiveness and tolerability for VZV-IgG in the adjuvant treatment of immunocompromised HZ patients and supports early intensification of HZ therapy in patients at high risk of severe disease progression.
CRIS-Team Scopus Importer:2023-09-22
Keywords: Generalized lesions; Herpes zoster; Hyperimmunoglobulin; Immunocompromised; Varitect CP; VZV; VZV-IgG